THIAMINE DEFICIENCY AND ITS MANAGEMENT IN CRITICAL STATES - V. V. Lomivorotov; M. N. Deryagin; M. N. Abubakirov; E. V. Fominskiy; V. A. Nepomnyaschikh (Вестник анестезиологии и реаниматологии, 2018)
The level of thiamine in critically ill patients can be low due to the loss of fluid, nutrition disorders and increased metabolism. The deficiency of thiamine is associated with reduction of respiratory metabolism, increase in lactate level and hypotension. At present, there are no clear evidence that all critically ill patients suffer from thiamine deficiency and face the risk to develop complications associated with thiamine deficiency. However, there is a certain correlation between progressing of thiamine deficiency and deterioration of the patient's state, though it is to be proved. The efficiency of treatment with thiamine is still being discussed since there is no consensus about the group of patients to be treated, thiamine doses and duration of treatment. For successful diagnostics and prediction of clinical outcomes related to thiamine deficiency, it is necessary to adopt standard methods for thiamine tests and the reference analytic method.